Social skills success for students with autism/Asperger's : helping adolescents on the spectrum to fit in - Frankel, Fred, 1946-; Wood, Jeffrey J., 1972- (San Francisco, CA. : Jossey-Bass, 2012)
'The only evidence-based program available for teaching social skills to adolescents with autism spectrum disordersTwo nationally known experts in friendship formation and anxiety management address the social challenges faced by adolescents with autism spectrum disorders (ASD). The book helps educators instruct youth on conversing with others, displaying appropriate body language, managing anxiety, initiating and participating in get-togethers, and more. The book is filled with helpful information on ASD to aid teachers who have received little training on the topic. Extremely practical, the book includes lesson plans, checklists, and sidebars with helpful advice. Based on UCLA's acclaimed PEERS program, the only evidence-based approach to teaching social skills to adolescents with ASD Contains best practices for working with parents, which is the key to helping kids learn social skills The authors discuss the pros and cons of teaching students with ASD in educational settings like full inclusion (good for academics but bad for social skills) and pull-out special day classes (where the reverse is true) Provides a much-needed book for teachers at all levels for helping students develop the skills they need to be successful'--
Includes bibliographical references and index.
Keywords: Youth with autism spectrum disorders -- Education; Youth with autism spectrum disorders -- Behavior modification; Social skills in adolescence